Pilar Logika dalam Membangun Ilmu Pengetahuan dan Manajemen Dakwah: Kajian Tentang Penggolongan, Definisi dan Analogi - Sakilah Sakilah; Wardati, Umu; Suryandari, Meity (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the role of classification, definition, and analogy as logical pillars that constitute the fundamental framework of knowledge. These three instruments of logic are closely interconnected in supporting the process of scientific reasoning. Classification functions to organize objects or phenomena into systematic categories, thereby facilitating identification. Definition provides clear boundaries of meaning to prevent conceptual ambiguity and ensure consistency of interpretation among researchers and practitioners. Meanwhile, analogy serves as a reasoning tool that bridges existing knowledge with new insights through rational comparison. This article employs a descriptive qualitative approach with a literature review of both classical and modern logic theories. The findings indicate that the integration of classification, definition, and analogy not only strengthens the consistency of scientific reasoning but also contributes significantly to education, communication, and the development of interdisciplinary knowledge. Thus, these three pillars of logic hold a strategic position in building a foundation of rationality and promoting the advancement of knowledge that is both comprehensive and applicablee.